2013
DOI: 10.1515/astro-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Dependence of Different Colors for the Apparent Magnitude-Limited Main Galaxy Sample of the SDSS DR7

Abstract: The apparent magnitude-limited Main galaxy sample of the Sloan Digital Sky Survey Data Release 7 is used to investigate the environmental dependence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Overall, the result of Deng (2012) showed that the environmental dependence of galaxy luminosities is very strong in the redshift region 0.02 ≤ z ≤ 0.10. Combining with the results from Deng et al (2012cDeng et al ( , 2013, one can also observe that in the apparent-magnitude limited Main galaxy sample the environmental dependence of galaxy properties becomes weak with increasing redshift. Table 1 also shows that in the high redshift region, the KS probability of all five band luminosities rises considerably with increasing redshift.…”
Section: Statistical Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Overall, the result of Deng (2012) showed that the environmental dependence of galaxy luminosities is very strong in the redshift region 0.02 ≤ z ≤ 0.10. Combining with the results from Deng et al (2012cDeng et al ( , 2013, one can also observe that in the apparent-magnitude limited Main galaxy sample the environmental dependence of galaxy properties becomes weak with increasing redshift. Table 1 also shows that in the high redshift region, the KS probability of all five band luminosities rises considerably with increasing redshift.…”
Section: Statistical Resultssupporting
confidence: 74%
“…Following our previous works (e.g., Deng 2012; Deng et al 2012cDeng et al , 2013Deng & Zou 2014a), we measure the projected local density Σ 5 , which is computed from the distance to the 5th nearest neighbor within a redshift slice of ± 1000 km s −1 of each galaxy (e.g., Goto et al 2003;Balogh et al 2004a,b), and divide the LOWZ sample into subsamples with a redshift bin size of ∆z = 0.01. In each subsample, we arrange galaxies in density order from the smallest to the largest, select approximately 5% of the galaxies, construct two samples at both density extremes according to the density, and compare the distributions of all five band luminosities in the lowest density regime with those in the densest regime.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 3 more Smart Citations